Analisa Strategi Pemasaran Untuk Meningkatkan Penjualan Produk Pada Industri Mebel â€œTâ€ Desa Poka Kecamatan Teluk Ambon Provinsi Maluku - Wa Emi Nurlette; Sherly Rutumalessy; Gilbert Alvin Rumalatu (P3M Politeknik Negeri Ambon, 2024)
The furniture industry is a type of business whose products can be marketed and are able to compete in the world of market competition. And that is what happened to